A strategic framework for the development and enhancement of safety culture in the artificial tanning sector in Greece. (31st August 2018) - Petri, A; Karabetsos, E
Abstract: Herein, a strategic framework for the development and enhancement of safety culture in the artificial tanning sector in Greece is presented. This framework has been designed and promoted by the competent national regulatory authority, which is the Greek Atomic Energy Commission (EEAE). The aim is to ensure a common understanding regarding ultraviolet radiation (UVR) and artificial tanning among artificial tanning professionals, stakeholders and the general public. The strategic framework is founded on the recommendations of international organizations, EU requirements and the relevant technical standards. It comprises three autonomous but interconnected components: (A) a sunbed operators' e-training course and certification process; (B) a code of practice addressed individually to business owners, sunbed operators and sunbed users; (C) communication strategies aiming to raise awareness regarding UVR and artificial tanning among all interested parties. The artificial tanning safety culture framework presented here is the policy option undertaken by the EEAE and is embedded in the upcoming legislation and regulations for the provision of artificial tanning services in Greece. EEAE considers that the structure of the artificial tanning safety culture strategic framework will serve as a guide for the development and promotion of relevant strategic safety culture frameworks for the provision of aesthetic/wellness services utilising other non-ionising radiation sources, which do not currently exist.